2007
DOI: 10.1523/jneurosci.4212-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Integration of Visual and Preparatory Signals in the Superior Colliculus during Saccadic Programming

Abstract: Efficient behavior requires that internally specified motor plans be integrated with incoming sensory information. Motor preparation and visual signals converge in the intermediate and deep layers of the superior colliculus (SC) to influence saccade planning and execution; however, the mechanism by which these sometimes conflicting signals are combined remains unclear. We studied this issue by presenting visual distractors as monkeys prepared saccades toward an upcoming target whose timing and location were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
129
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 54 publications
26
129
2
Order By: Relevance
“…10), which indicates that the SCi is causally involved in selecting strategic saccades. Previous work has shown that artificially manipulating SCi activity can bias the selection of perceptually guided saccades; that is, alter the probability of choosing a target stimulus that differs from distracting stimuli based on some sensory feature McPeek and Keller, 2004;Dorris et al, 2007). This study extends these previous findings in two important respects.…”
Section: Artificially Manipulating Saccade Selectionsupporting
confidence: 74%
See 1 more Smart Citation
“…10), which indicates that the SCi is causally involved in selecting strategic saccades. Previous work has shown that artificially manipulating SCi activity can bias the selection of perceptually guided saccades; that is, alter the probability of choosing a target stimulus that differs from distracting stimuli based on some sensory feature McPeek and Keller, 2004;Dorris et al, 2007). This study extends these previous findings in two important respects.…”
Section: Artificially Manipulating Saccade Selectionsupporting
confidence: 74%
“…This transient burst had to be at least 50 spikes/s above the activity during preparatory period outlined above and be initiated within 100 ms after presentation of the target (Dorris et al, 2002). This visual activity was not contaminated by saccade-related bursts because the initiation of saccades was delayed during the mixed-strategy task presumably because of the competitive interactions between the two simultaneously presented targets (Dorris et al, 2007). Last, all microstimulation experiments were conducted within SCi regions with identified saccade-related activity.…”
Section: Neuronal Classificationmentioning
confidence: 99%
“…Numerous cortical areas are implied in the cortical network of saccadic movement such as frontal eye field (FEF), supplementary eye field, dorsolateral prefrontal cortex, parietal eye field, cerebellum and different subcortical regions as the superior colliculus and the brainstem reticular formation (Gaymard et al, 1998;Quaia et al, 1999;Munoz and Fecteau, 2002;Dorris et al, 2007). Previous studies suggest that the forward and inverse models used for sensory-motor control involve the cerebellum and parietal cortex (Zee et al, 1980;Imamizu et al, 2004;Bursztyn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Visual, DLPFC, and FEF inputs to SC show a coarse topology, in that cortical cells tend to project to many neighboring neurons in SC (Funahashi et al 1990;Komatsu and Suzuki 1985;Lock et al 2003;Sommer and Wurtz 2001). This implies that collicular neurons have relatively broad visual fields, which is indeed the case (Dorris et al 2007;Ottes et al 1986;Schiller et al 1980). The spatial shape of the inputs to SC was a Gaussian around an SC location receiving maximum input l max .…”
Section: Topology Of Inputsmentioning
confidence: 97%